Effects of the Addition of Co or Ni Atoms on Structure and Magnetism of FeB Amorphous Alloy: Ab Initio Molecular Dynamics Simulation - Shuwei Lu (MDPI AG, 2021)
The effects of the substitution of Fe by Co or Ni on both the structure and the magnetic properties of FeB amorphous alloy were investigated using first-principle molecular dynamics. The pair distribution function, Voronoi polyhedra, and density of states of Fe80−xTMxB20 (x = 0, 10, 20, 30, and 40 at.%, TM(Transition Metal): Co, Ni) amorphous alloys were calculated. The results show that with the increase in Co content, the saturation magnetization of Fe80−xCoxB20 (x = 0, 10, 20, 30, and 40 at.%) amorphous alloys initially increases and then decreases upon reaching the maximum at x = 10 at.%, while for Fe80−xNixB20 (x = 0, 10, 20, 30, and 40 at.%), the saturation magnetization decreases monotonously with the increase in Ni content. Accordingly, for the two kinds of amorphous alloys, the obtained simulation results on the variation trends of the saturation magnetization with the change in alloy composition are in good agreement with the experimental observation. Furthermore, the relative maximum magnetic moment was recorded for Fe70Co10B20 amorphous alloy, due to the induced increased magnetic moments of the Fe atoms surrounding the Co atom in the case of low Co dopant, as well as the increase in the exchange splitting energy caused by the enhancement of local atomic symmetry.